Perancangan UI/UX Smart Aset dan Infrastruktur Jaringan Universitas Teknokrat Indonesia: Pendekatan Human Centered Design - Ratih Siti Jamilah; Donaya Pasha (STMIK Budi Darma, 2024)
The rapid development and advancement of technology, the application of the Smart Asset Spatial and Network Infrastructure application system is the main strategy in increasing the use of technology in various institutions such as companies and educational institutions. The application of this system aims to provide convenience and efficiency in managing records related to the assets of Universitas Teknokrat Indonesia. This research involves the process of Problem Identification, Literature Study, and Application of the Human Centered Design (HCD) method. Where the process of designing the UI / UX application of Smart Asset Layout and Network Infrastructure of Universitas Teknokrat Indonesia using the HCD method because of the approach that incorporates the needs, goals, and aspirations of users into the design process to create solutions that are more relevant, effective, and satisfying for users. UI/UX Design of Smart Spatial and Infrastructure Asset Applications Using the HCD Method with the aim of designing application designs and prototypes as a determination of the design process that has been made and through the prototype stage the author can find out feedback information from users (students) of Universitas Teknokrat Indonesia. The Human Centered Design (HCD) method has three stages, namely inspiration, ideation, and implementation. By doing this application design, it will provide convenience to students and campus staff in carrying out the existing spatial management system at Universitas Teknokrat Indonesia. The conclusion of the results of this study using the HCD method obtained the number of respondents as many as 33, then had a respondent result of 78.1% of the Class of 2020, namely where this application is effective and needed by students in facilitating the Spatial system and Network Infrastructure of Universitas Teknokrat Indonesia.